Tapioca pearls made from carrotts - Allayne M. Angoluan, Jericho Dec M. Aricayos, Evie-Jane T. Bajar, Ashley Andrei P. Dela Rosa, Verlizza Rhina G. Ganotice, Cherlyn B. Revadulla, Loriebeth P. Ruiz, Ma. Jona Rosa S. Valbuena 4 0 16; 5
u
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2022
Keywords: 2 -- 0; 6; 20; 20; 2